Impedance-based sensitivity analysis for enhanced dynamic stability in DC off-grid hydrogen production systems - Chenguang Zhang; Zhongjian Kang; Bin Li; Hongyang Zhang; Di Zhu (Energy Conversion and Management: X)
DC off-grid hydrogen production systems, employing source–hydrogen interface converters to achieve efficient renewable energy conversion and electrolysis coupling, represent a core technological solution for green hydrogen generation. However, strong control coupling and nonlinear characteristics between the interface converter and electrolysis units complicate multi-operational stability analysis, significantly increasing parameter optimization challenges. This study proposes a novel impedance-based global sensitivity analysis (GSA) framework to quantitatively evaluate converter impedance parameters’ impacts on dynamic stability, enabling precise optimization of dominant variables for enhanced stability margins. The interface converter adopts dual active bridge (DAB) configurations with input-parallel-output-series (IPOS) and input-series-output-parallel (ISOP) topologies. Methodologically, an impedance model integrating source–load-storage hydrogen production components was developed and validated through frequency-sweep experiments. Subsequently, cumulative distribution functions (CDFs)-based GSA identified stability-critical parameters while impedance ratio and Nyquist criteria established dynamic stability boundaries. Experimental validation across multiple operational scenarios confirmed stable operating regions of converter impedance parameters, demonstrating method effectiveness. This research provides systematic solutions for stability enhancement and parameter optimization in off-grid hydrogen systems.